Islamic-Based Human Resource Management Strategy at Phatna Witya School, Yala, South Thailand - Nimong, Tuanchulfan; Amsari, Syahrul (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to investigate the management of human resources based on Islamic principles as implemented at Phatna Witya School in Yala, Southern Thailand. HR management that aligns with Islamic teachings not only focuses on skills and professionalism but also emphasizes spiritual aspects, ethics, and moral responsibilities derived from Islamic teachings. This research employs a qualitative methodology through a case study approach. Data were collected through in-depth interviews, observations, and document gathering. Participants in this study included the school principal, vice principal, teachers, and other educational staff. The findings reveal that the Islamic-based HR management approach at Phatna Witya School in Yala includes HR planning that adheres to Islamic values, a recruitment and selection process that pays attention to both competency and Islamic ethics, development of employees in spiritual and professional dimensions, and a performance assessment system that balances worldly and spiritual matters. This approach is seen as effective in shaping individuals with integrity, discipline, and a strong emphasis on Islamic values.